The plasma virome in longitudinal samples from pregnant patients - Stout, Molly J.; Brar, Anoop K.; Herter, Brandi N.; Rankin, Ananda; Wylie, Kristine M. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Nucleic acid from viruses is common in peripheral blood, even in asymptomatic individuals. How physiologic changes of pregnancy impact host-virus dynamics for acute, chronic, and latent viral infections is not well described. Previously we found higher viral diversity in the vagina during pregnancy associated with preterm birth (PTB) and Black race. We hypothesized that higher diversity and viral copy numbers in the plasma would show similar trends. Methods To test this hypothesis, we evaluated longitudinally collected plasma samples from 23 pregnant patients (11 term and 12 preterm) using metagenomic sequencing with ViroCap enrichment to enhance virus detection. Sequence data were analyzed with the ViroMatch pipeline. Results We detected nucleic acid from at least 1 virus in at least 1 sample from 87% (20/23) of the maternal subjects. The viruses represented 5 families: Herpesviridae, Poxviridae, Papillomaviridae, Anelloviridae, and Flaviviridae. We analyzed cord plasma from 18 of the babies from those patients and found nucleic acid from viruses in 33% of the samples (6/18) from 3 families: Herpesviridae, Papillomaviridae, and Anelloviridae. Some viral genomes were found in both maternal plasma and cord plasma from maternal-fetal pairs (e.g. cytomegalovirus, anellovirus). We found that Black race associated with higher viral richness (number of different viruses detected) in the maternal blood samples (P=0.003), consistent with our previous observations in vaginal samples. We did not detect associations between viral richness and PTB or the trimester of sampling. We then examined anelloviruses, a group of viruses that is ubiquitous and whose viral copy numbers fluctuate with immunological state. We tested anellovirus copy numbers in plasma from 63 pregnant patients sampled longitudinally using qPCR. Black race associated with higher anellovirus positivity (P<0.001) but not copy numbers (P=0.1). Anellovirus positivity and copy numbers were higher in the PTB group compared to the term group (P<0.01, P=0.003, respectively). Interestingly, these features did not occur at the time of delivery but appeared earlier in pregnancy, suggesting that although anelloviruses were biomarkers for PTB they were not triggering parturition. Discussion These results emphasize the importance of longitudinal sampling and diverse cohorts in studies of virome dynamics during pregnancy.